PENGEMBANGAN MEDIA INTERAKTIF BERBANTUAN CANVA DENGAN MODEL PBL UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATERI RANTAI MAKANAN DI KELAS V SD - Girsang, Farhan Alfath; Hidayat, Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The research conducted aims to develop an interactive media assisted by Canva using the PBL model to increase students' interest in learning food chain material in grade V of elementary school. This research is a Research and Development (R&D) study conducted using the 4D development procedure. To collect the required data, the researcher used a validation questionnaire given to several expert validators and a student learning interest questionnaire to measure students' interest in learning before and after using the developed media. From the results of the media expert validation, a validity score of 84 was obtained with the criteria "Very Eligible" and from the material expert validation, a validity score of 89.2 was obtained with the criteria "Very Eligible". Before the learning process using interactive media assisted by Canva with the PBL model, it was known that the student's learning interest score was only 68.16 with the criteria "Good". After the learning process was carried out in grade V of Elementary School 060818 Medan Denai using interactive media assisted by Canva with the developed PBL model, the student's learning interest score became 81.04 with the criteria "Very Good".